1975
DOI: 10.1007/bf01912025
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of organic compounds. Note III

Abstract: Calorimetric and cryometric methods are employed to measure the enthalpies of fusion and prefusion of some organic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The agreement between the cryoscopic and calorimetric values of AHf is satisfactory (Table 1) In Table 2 ~'f, as defined previously [2], is reported for the paraffins, monocarboxylic acids and amides (even series); it is evident that the melting entropy per Cnumber decreases in the order paraff• monocarboxylic acids, amides. The agreement between the cryoscopic and calorimetric values of AHf is satisfactory (Table 1) In Table 2 ~'f, as defined previously [2], is reported for the paraffins, monocarboxylic acids and amides (even series); it is evident that the melting entropy per Cnumber decreases in the order paraff• monocarboxylic acids, amides.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The agreement between the cryoscopic and calorimetric values of AHf is satisfactory (Table 1) In Table 2 ~'f, as defined previously [2], is reported for the paraffins, monocarboxylic acids and amides (even series); it is evident that the melting entropy per Cnumber decreases in the order paraff• monocarboxylic acids, amides. The agreement between the cryoscopic and calorimetric values of AHf is satisfactory (Table 1) In Table 2 ~'f, as defined previously [2], is reported for the paraffins, monocarboxylic acids and amides (even series); it is evident that the melting entropy per Cnumber decreases in the order paraff• monocarboxylic acids, amides.…”
Section: Resultssupporting
confidence: 68%
“…Recently the thermodynamic properties of fusion of some aliphatic acids [1,2] have been discussed and related [2,3] to their structural properties. The results of similar research on two amides are reported in this note.…”
mentioning
confidence: 99%
“…ofC-R which, as demonstrated \OH... in preceding papers [1,2] is the structural entity of the fusion. The length [6] 12 is calculated in the following way: where N is Avogadro's number and 7 represents the number of cylinders contained in each hexagonal prism.…”
Section: Discussionmentioning
confidence: 92%
“…The fusion entropies of these acids [1,2] are a linear function of the parameter (b -Vp,r,l. ), i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation